Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 13 - Cumulative Review - Page 970: 43


$-6\sqrt[3] 2$

Work Step by Step

$\sqrt[3] {54}-5\sqrt[3] {16}+\sqrt[3] 2$ =$\sqrt[3] {27\times2}-5\sqrt[3] {8\times2}+\sqrt[3] 2$ =$(\sqrt[3] {27}\times\sqrt[3] 2)-5(\sqrt[3] {8}\times\sqrt[3] 2)+\sqrt[3] 2$ =$(3\times\sqrt[3] 2)-5(2\times\sqrt[3] 2)+\sqrt[3] 2$ =$3\sqrt[3] 2-10\sqrt[3] 2+\sqrt[3] 2$ =$(3-10+1)\sqrt[3] 2$ =$-6\sqrt[3] 2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.